KONTRIBUSI PEMERINTAH DALAM PENGEMBANGAN INDUSTRI MEDIA DIGITAL DI MASYARAKAT (KAJIAN DI JAWA BARAT INDONESIA) - Edwin Rizal; Rully Khairul Anwar (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2017)
This study traces government efforts in formulating action programs in the development ofcommunity industries conducted in digital media. The government contribution here aims to inviteand provide models of economic growth, including in the field of micro, small and mediumenterprises in the field of media industry. This can be a potential that can provide prosperity forthe community in a sustainable manner. This is where the need for formulation of communitybaseddigital media development of the government of West Java. With the formulation, it isquestionable whether the government can bring the community to the digital media industry so asto foster the creative economy of society, how the processes that occur in the formulation of actionprograms, and similar questions. With descriptive and qualitative methods, this study found thatthe government has formulated policies that strongly support the development of the digital mediaindustry, as well as the general public has responded positively to government policies that haveadvocated the development of cutting-edge technology in the business field, but there are stillconstraints technical issues that must be continually refined.